Inhibitory Effect of Puroindoline Peptides on Campylobacter jejuni Growth and Biofilm Formation - Talukdar, Prabhat K.; Turner, Kyrah L.; Crockett, Torin M.; Lu, Xiaonan; Morris, Craig F.; Konkel, Michael E. (Frontiers in Microbiology, 2021)
Puroindolines are small, amphipathic, wheat proteins that determine the hardness of the wheat kernel and protect crops from different pathogens. Puroindoline A (PinA) and puroindoline B (PinB) are two major isoforms of puroindolines. These proteins have antibacterial and antifungal properties mainly attributed to their characteristic tryptophan-rich domains (TRDs). In this study, we investigated the antimicrobial effect of PinA and PinB synthetic peptides against the growth and biofilm formation of Campylobacter jejuni. C. jejuni is an important microaerobic, foodborne pathogen that causes gastrointestinal and neurological diseases in humans. Our results showed that: 1) PinA, but not PinB, has strong antimicrobial activity against C. jejuni clinical strains 81-176 and F38011, Escherichia coli O157:H7, methicillin-resistant Staphylococcus aureus, Salmonella enterica serovar Typhimurium, and Listeria monocytogenes; 2) The substitution of two tryptophan residues to glycine (W G) in the TRD of PinA abolishes its antimicrobial activity against these microorganisms; 3) PinA functions additively with two common antibiotics (ciprofloxacin and erythromycin) to inhibit or inactivate C. jejuni strains; 4) PinA damages the C. jejuni cellular membrane, 5) PinA is cytotoxic to mammalian INT 407 cells at high concentrations; and 6) PinA inhibits C. jejuni biofilm formation. In summary, this study demonstrates the antimicrobial activity of PinA against C. jejuni growth and biofilm formation and further confirms the potential use of PinA as a therapeutic agent in health care or as preservatives in agri-food industry.